Computer Based Test pada Sekolah Menengah Pertama - Farida Febriati (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The program of community Partnership (PKM) activities are carried out at Junior High School (SMP) Negeri 3 Sinjai.The identification of partner problems were SMP in Sinjai district especially in SMP Negeri 3 Sinjai has not used CBT for dailyassessment, but is only limited to the national exam. The purpose of this PKM activity is to train junior high school teachers inSinjai Regency to be able to use and utilize CBT in learning evaluation and to find out applications that can be used for CBTtests. This PKM activity was carried out for 3 days with 25 participants and 3 assistants. The results obtained from this trainingactivity indicate that, are 1) Computer Based Test application programs 2) Teachers and educators can use the Computer BasedTest application programs. The factors faced in the implementation of this activity are the internet connection in the schoolenvironment which is only at points and teachers and educators still need technical guidance to use the Computer Based Testapplication program.